The FRG's import market for manufactured products : CMEA, Southern European and developing countries - Inotai, András. (Budapest : Hungarian Scientific Council for World Economy, 1982)
This study examined the behavior of the West German import market in the first half of the seventies and the activity of the CMEA countries in the market.
Competition of CMEA, southern European and rapidly industrializing countries in the West German import market for manufactured products in the second half of the seventies.
II 17/01/2019
Loans
Keywords: Competition, International; Germany (West); Developing countries; Europe, Southern; Communist countries